Relating vibrational energy with Kekulé‐ and Clar‐structure‐based parameters. Issue 7 (7th December 2021) - Radenković, Slavko; Redžepović, Izudin; Đorđević, Slađana; Furtula, Boris; Tratnik, Niko; Žigert Pleteršek, Petra
Abstract: For all possible catacondensed Kekuléan molecules having four, five, and six hexagons, the molecular vibrational energies were calculated within the harmonic approximation at the HF, B3LYP, and M06‐2X levels of theory in combination with the 6‐311G(d, p) basis set. The obtained vibrational energies were found to be a linear function of the Kekulé structure count K within the sets of isomeric molecules. By employing the recently introduced generalized Zhang–Zhang polynomial, it was shown that the molecular vibrational energies can be related to the Clar‐structure‐based parameters. The obtained approximate formulas can accurately reproduce the vibrational energies with an average absolute error less than 1 kJ/mol. In addition, these formulas can provide further details on the structural dependence of molecular vibrational energies. Abstract : Molecular vibrational energies calculated within the harmonic approximation at the HF and DFT levels of theory were found to be a linear function of the Kekulé structure count within the sets of isomeric benzenoid hydrocarbons. The obtained approximate formulas can accurately reproduce the vibrational energies with an average absolute error less than 1 kJ/mol.